Multi-objective fuzzy optimization of space trusses by Ms-Excel - Kelesoglu, O; Ulker, M (Elsevier Sci Ltd, 2005)
In this study space truss systems were design optimized by using fuzzy sets. For this aim lambda formulation was applied. The analysis of the truss system is made with respect to matrix-displacement method. The algorithm of multi-objective fuzzy optimization was formed using the macros of Ms-Excel. A number of design examples are presented to demonstrate the application of the algorithm. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: space truss; fuzzy sets; membership function; multi-objective; fuzzy optimization; spreadsheet